Eksistensi Partai Politik Lokal di Provinsi Papua Pasca Putusan Mahkamah Konstitusi Nomor 41/PUU-XVII/2019 - Galih Raka Siwi; Reviansyah Erlianto; Maharani Nurdin (Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2021)
The existence of local political parties in Indonesia is a tangible form of the existence of special autonomy in a certain area. The specificity of a certain area is regulated in the 1945 Constitution Article 18B paragraph (1). In addition, the formation of local political parties is one of the human rights in the political field, as stated in Article 28E paragraph (3) of the 1945 Constitution. The research method uses a normative juridical approach with secondary data and analyzed descriptively qualitatively. Based on research, Papua Province has the right to form political parties (see Article 28 paragraph (1) of the Papua Province Special Autonomy Law). However, the phrase